Absence of prolactin gene expression in colorectal cancer. Issue 3 (1st June 1999) - Wood, A J; Thomas, C M; Baumforth, K R; Flavell, J R; Scott, K W; Grace, R H; Williams, J G; Holland, M R; Dunn, R; Jacobs, A G; Harrison, A; Brun, S; et al.
Abstract : AIMS: Previous studies documenting hyperprolactinaemia in patients with colorectal cancer have suggested that the tumour is the source of hormone production. The aim of this study was to determine the frequency of hyperprolactinaemia in patients with colorectal cancer before, during, and after surgery, and also to determine whether prolactin is produced by these tumours. METHODS: Serum prolactin concentrations were measured in 20 patients with colorectal cancer before, during, and after surgical resection of their tumours. Samples taken during surgery included peripheral venous blood and blood taken from the main veins draining the tumour. To determine whether the tumour was responsible for the production of prolactin in these patients, paraffin wax embedded sections of tumour specimens were subjected to immunohistochemistry and western blotting using a monoclonal antibody to prolactin. RESULTS: Five patients (three women, two men) had preoperative prolactin concentrations above the normal reference range, although this increase was of clinical importance in only two. After surgical resection of their tumours, prolactin concentrations remained high in both patients. All 20 patients had greatly raised prolactin values at the time of surgery, irrespective of whether this was measured in peripheral blood or in blood taken from veins draining the tumour. All 20 colorectal cancer tissue samples, including those with raised preoperative and/or postoperative prolactin concentrations, were negative for prolactin staining. Frozen tissue was also available in four cases. The absence of prolactin gene expression in these four tumours was confirmed both by repeat immunohistochemistry and by western blotting. A further 50 colorectal cancer cases examined by immunohistochemistry alone were also unreactive for prolactin. CONCLUSIONS: The results of this study suggest that serum prolactin concentrations may occasionally be raised in colorectal cancer patients, but that the tumour is not the source of hormone production.